Pengaruh Model Example Non Example Berbantukan Media Powtoon terhadap Hasil Belajar Matematika Siswa Kelas IV SD - Nursafiri, Mellynia Dwi; Kusumawati, Naniek; Retno, Raras Setyo (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2022)
This study aims to determine the effect of the Example Non Example model with the help of Powtoon media on the mathematics learning outcomes of fourth-grade students at SDN 01 Taman. This type of research is experimental quantitative research. This research method Experiment Design with Pretest-Posttest Control Group Design. This study took two classes as samples: class IV A as the experimental class and class IV B as the control class. Sampling using Simple Random Sampling. The technique of collecting data on mathematics learning outcomes uses interviews, observations, tests and documentation. From the data analysis using the t test, it is known that ttable = 2.069 for 5% with dk = 25, if tcount = 5.784 > ttable = 2.069 then H0 is rejected and H1 is accepted. Thus it can be said that the influence of the Example Non Example model with the help of Powtoon media affects the mathematics learning outcomes of fourth-grade students at SDN 01 Taman